Prediction of Impacts on Public Health: Analysis of Environmental Impact Reports Submitted to IBAMA (2012-2022) (Global Journal of Human-Social Science, 2024)
This article of an analytical and exploratory nature aimed to evaluate the frequency of the impacts on public health component in the Environmental Impact Reports EIR submitted to the Brazilian Institute of the Environment IBAMA to obtain environmental licenses To meet this objective we made a random selection of RIMA submitted to IBAMA to obtain environmental licensing between the years 2012 and 2022 regardless of the type of project totaling 10 RIMA analyzed When reviewing the RIMA the documents were read in full We then sought to identify in the RIMA 1 the inclusion of Impacts on Public Health and associated risks 2 the adoption of some type of methodological tool for health impact assessment AIS and 3 the incorporation of a health professional in the technical team that prepared the RIMA The results point to 1 a pattern of absence of health impact assessment methodologies clearly identified in the RIMA 2 the Terms of Reference themselves are vague regarding the criteria involving impacts on human health that guide the EIA-RIMA 3 there is a systematic absence of professionals in the areas of Health Sciences in teams that produce EIA-RIMA
Keywords: health impact assessment; environmental licensing; public health